A case study of collaboration among the ESP practitioner, the content teacher, and the students - Almagro Esteban, Ana; Vallejo Martos, Manuel Carlos (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2002)
The literature in the field of ESP (English for Specific Purposes) conspicuously documents the relevance of the collaboration between the teacher in this field and the content teacher, as well as that between the former and the student. However, the positions on this score are of a general nature and, consequently, cannot easily be put into practice. This has led us to analyze the main aspects determining this collaboration, and the way in which it can be implemented. In order to do so, we will take as a reference point a post-graduate course on Foreign Trade and, by extension, on Management internationalization. We start by describing the ESP teacher's profile, and following upon this, we introduce the theoretical framework of the present study. In turn, we give way to the contextualization of the course under scrutiny, which will allow us to describe how this collaboration was undertaken building upon Dudley-Evans and St John's (1998) view. Finally, we highlight the conclusion at which our paper has enabled us to arrive, namely, that the collaboration between both teachers builds progressively and that it has to be established by delimiting their role in it, that the students' collaboration always involves some risks we should assume and, finally, that teachers with a philological background have a great deal to bring to the ESP field.